INCREASING STUDENT UNDERSTANDING ON PPKN STUDY THROUGH THE DEBATE MODEL TO THE LEGISLATION MATERIALS - Rosmiati, Yatti (Jurnal Administrasi Pendidikan, 2024)
This Classroom Action Research aims to improve the learning outcomes and activities of class VIII A students in PPKn lessons on legislation material through the application of debate learning models. The results of the pre-research obtained an average score of 55.87, completed 2 people or 5%. After reflection, the average score in cycle II increased to 86.34 in the "Very Good" category, completed 38 people or 95%. The increase in the average score from the pre-test to cycle I was around 19. The increase in the percentage of achievement of the KKM score from the pre-test to the cycle was around 50%. It can be concluded that the application of the debate learning model is effective in the PPKn learning process on legislation material because it can significantly increase student activity and learning outcomes. The obstacles found in this study were that it took time, extra energy, and patience from the teacher, and overall parents and guidance were less than optimal.